Bactericidal Effects of Pulsed-Light Treatment Against Burkholderia gladioli pv. cocovenenans in Auricularia: Mechanisms and Influences - Chen Niu; Jin Hao; Zeyu Hu; Yuchen Song; Yilin Ren; Yuanchun Wu; Jing Yang; Zihan Song; Yahong Yuan; Tianli Yue (Foods)
Auricularia (wood ear fungus) is susceptible to Burkholderia gladioli pv. cocovenenans (BGC) and causes food poisoning. This study investigated pulsed-light (PL) inactivation of BGC on Auricularia. The evaluation of PL parameters indicated that lower initial biomass, shorter distance, and more fluences were more effective in inactivating BGC. This study achieved 5~8 Log reductions in BGC in phosphate-buffered saline and ~4 Log reductions in Auricularia auricula and Auricularia cornea var. Li, and the survivor curves fit the Weibull model well with R2 values of 0.943~0.987 and RMSE values of 0.308~0.430 in all three substrates. PL caused cell membrane damage, leading to DNA, protein, and ATP leakage and increased ROS production. PL caused an alteration in color (ΔE 3.01~7.67) but not springiness and cohesiveness in the texture of Auricularia at 11.80~35.40 J/cm2. In all, PL is effective in inactivating BGC on the surface of Auricularia at 35.40 J/cm2 and can be taken as a good controlling measure.